The Role of Profitability and Environmental Performance in Affecting Carbon Emission Disclosure with Media Exposure as Moderation - Ajeng Puspitasari; Enny Susilowati Mardjono; Anna Sumaryati; Nila Tristiarini (Universitas Muhammadiyah Semarang, 2026)
This study examines how profitability and environmental performance affect the level of carbon emissions disclosure among energy sector companies listed on the Indonesia Stock Exchange. It also considers the role of media exposure in influencing this relationship. It looks at 107 sets of observational data from the years 2019 to 2024. Data analysis is conducted in EViews 13; the analysis uses panel data and applies a Random Effects Model along with Moderated Regression Analysis (MRA). The results show that how well an organization takes care of the environment has a big impact on how much it shares information about its carbon emissions, and this connection becomes even stronger when the organization is covered by the media. Meanwhile, profitability has no effect, and media exposure does not moderate the relationship. This research contributes by demonstrating that public pressure through media exposure is more effective in encouraging environmental transparency than internal economic motivation (profitability) and acts as a catalyst that strengthens positive corporate signals to reduce information asymmetry. In practice, these findings inform regulators in optimizing the publication of environmental performance ratings as an external oversight instrument to improve carbon accountability in the energy sector.